Genetic origin of sporadic cases and RNA toxicity in neuronal intranuclear inclusion disease. Issue 5 (25th March 2021) - Deng, Jianwen; Zhou, Binbin; Yu, Jiaxi; Han, Xiaochen; Fu, Jianhui; Li, Xiaobin; Xie, Xufang; Zhu, Min; Zheng, Yilei; Guo, Xueyu; Li, Pidong; Wang, Qingqing; et al.
Abstract : Background: GGC repeat expansion in NOTCH2NLC has been recently linked to neuronal intranuclear inclusion disease (NIID) via unknown disease mechanisms. Herein, we explore the genetic origin of the sporadic cases and toxic RNA gain-of-function mechanism in NIID. Methods: Multiple genetic screenings were performed on NIID individuals and their available family members. Methylation status of blood DNA, NOTCH2NLC mRNA level from muscle biopsies and RNA foci from skin biopsies of NIID individuals or asymptomatic carriers were evaluated and compared. Results: In two sporadic NIID families, we identified two clinically and pathologically asymptomatic fathers carrying large GGC repeat expansion, above 300 repeats, with offspring repeat numbers of 172 and 148, respectively. Further evaluation revealed that the GGC repeat numbers in the sperm from two asymptomatic fathers were only 63 and 98, respectively. The CpG island in NOTCH2NLC of the asymptomatic carriers was hypermethylated, and accordingly, the NOTCH2NLC mRNA levels were decreased in the asymptomatic fathers. GGC repeat expansion RNA formed RNA foci and sequestered RNA binding proteins into p62 positive intranuclear inclusions in NIID individuals but not in the control or asymptomatic carrier. Conclusion: Our study suggested the GGC repeat expansion in NOTCH2NLC might have a disease-causing number ranging from ~41 to ~300 repeats. The contraction of GGC repeat expansion in sperm could be a possible mechanism for the paternal-biased origin in some sporadic or recessive inherited NIID individuals. The toxic RNA gain-of-function mechanism was identified to be involved in the pathogenicity of this disease.